Innovative knowledge management concepts for organizational creativity and collaborative design - Eardley, Alan; Uden, Lorna 1946- (Information Science Reference, 2011)
"This book provides a valuable resource for promoting current academic discourse on innovation in knowledge-intensive organizations and contexts" - Provided by publisher
Includes bibliographical references and index
Keywords: Wissensmanagement; Aufsatzsammlung